Exploring viewpoints on Mountain Hay Meadow conservation: A Q-methodology investigation from Austria - Julian Janisch; Katharina Gugerell; Thomas Thaler; Valentin Fiala (Biological Conservation, 2026)

Structural evolution of the inverted Neoproterozoic Yeneena Basin, Australia - Chirantan Parui; Susanne Schmid; Giovanni Spampinato; Helen B. McFarlane; Valentin Zuchuat; Klaus Gessner; Heather A. Sheldon; Thomas Poulet (Precambrian Research, 2026)

Coverage varies, origin shifts: A review of 37 years of satellite-based sea-ice conditions around the HAUSGARTEN observatory - Valentin Ludwig; Thomas Krumpen (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Influence of hepatic steatosis on antiseizure drug metabolism: in vitro evidence from differentiated HepaRG cells - Valentin Plissonneau; Thomas Gicquel; Emma-Rose Legrand Brault; Jeremy Jost; Julie Massart; Brendan Le Daré (Toxicology Letters, 2026)

Overcoming the Challenges of Viscous Simulated Fed State Media with a Computerized Numerical Control Tablet Disintegration and Dissolution Tester - Valentin Stahl; Muhammad Farooq Umer; Jozef Al-Gousous; Thomas Nawroth; Wei-Jhe Sun; Fang Wu; Wenlei Jiang; Zongming Gao; Peter Langguth (AAPS PharmSciTech, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Fate of recently assimilated carbon in the soil–plant system of Vaccinium vitis-idaea and its response to warming in a 2.5-year translocation experiment - Valentin B. Kurbel; Outi-Maaria Sietiö; Kristiina Karhu; Andrei Rodionov; Sari Timonen; Thomas Ohnemus; Eva Lehndorff; Johanna Pausch; Nele Meyer (Plant and Soil, 2026)
Background and aims Shrubs like Vaccinium vitis-idaea substantially contribute to forest carbon (C) sequestration. Therefore, understanding their allocation patterns under climate change is crucial. We conducted a translocation experiment with 13 CO 2 pulse-labelling to test if (I) belowground pools accumulate total and recently assimilated C, (II) within fine roots, assimilated C is preferentially allocated to root tips and mycorrhized cells and (III), whether warming alters C allocation patterns. Methods We translocated soil cores with V. vitis-idaea from North- to South-Finland (+ 3.7 °C mean temperature). After 2.5 years, we excavated and pulse-labelled them with 13 CO 2 , tracing the 13 C in plant, soil, and respiration. We used laser-ablation isotope ratio mass spectrometry to examine 13 C distribution in fine roots. Results Roots represented the largest plant C pool (north: 49.69 ± 9.73%, translocated: 43.92 ± 6.59% of plant C stock). A substantial amount of recently assimilated 13 C was recovered belowground (roots + soil, north: 15.59 ± 5.77%, translocated: 39.21 ± 29.32%) 8 days after labelling. Most assimilated C was respired (north: 63.3 ± 5.9%, translocated: 44.1 ± 3.2%) or recovered in leaves (north: 17.9 ± 5.92%, translocated: 19.2 ± 3.19%). Within fine roots, 13 C content tended to be higher at root tips, while mycorrhizal infection had no effect. Warming tended to increase C allocation to the shoot and significantly decreased 13 C in the microbial biomass in the mineral soil. Conclusion V. vitis-idaea allocates a large portion of assimilates belowground, but 2.5 years of warming only marginally change C allocation patterns. Accelerated soil microbial processes after translocation may increase plant N availability, potentially affecting C allocation over longer time spans.

Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark; Valentin Thomas; Richard S. Taylor; Mathieu Charles; Audrey Laurent; Isabelle Schwartz-Cornil; Bertrand Collet; Delphine Lallias; Daniel J. Macqueen; Samuel A.M. Martin; Pierre Boudinot (Fish & Shellfish Immunology, 2025)

High-resolution building stock energy model for assessing the impact on the load curve of residential space heating electrification - Valentin Moreau; Marie-Hélène Laurent; Thomas Berthou; Bruno Duplessis; Pascal Stabat (Energy and Buildings, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Drivers of nest site selection and breeding success in an Alpine ground-nesting songbird - Yann Rime; Pius Korner; Barbara Helm; Thomas Müller; Valentin Amrhein; Felix Liechti; Christoph M. Meier (Journal of Ornithology, 2025)
Birds breeding in high-Alpine habitats must select a suitable breeding site and achieve successful reproduction within a restricted time. During four breeding seasons, we monitored nest sites of the Northern Wheatear ( Oenanthe oenanthe ), a high-Alpine long-distance migrant. We investigated how ecological factors predicted the selection of a site for nesting within the home range, using conditional logistic regression. Birds preferred south-exposed productive pastures on gentle slopes, interspersed with non-vegetated ground and human-made rockpiles. The direct vicinity of conspecific nests was avoided, as were shrubby or north-exposed areas. We investigated if habitat also influenced breeding success. We analysed the impact of environmental factors on breeding success, which was primarily driven by predation. The probability of the brood fledging successfully decreased on north-exposed slopes or on areas with low coverage of non-vegetated ground. The vicinity of conspecific nests did not have a clear effect. Further, we describe how breeding success varied within and between years. Within years, replacement broods had a higher breeding success. The apparent absence of variation in breeding success between years and a delay of the breeding period in the year with late spring onset suggest a high level of tolerance with respect to inter-annual variation of meteorological conditions. Since the preferred habitat is still widely available in the Alps and given the negative population trends in Western Europe, the Alpine range might serve as a refuge for the Northern Wheatear, as long as low-intensity management and heterogenous habitats are maintained.

Synergistic negative effects of ash dieback and Armillaria root rot on health and stability of mature ash trees - Philipp Spiegel; Thomas Hintze; Aaron Kopp; Mario Sahli; Andreas Detter; Valentin Queloz; Simone Prospero; Renate Heinzelmann (Forest Ecology and Management, 2025)

Evolutionary ecology of masting: mechanisms, models, and climate change - Michal Bogdziewicz; Dave Kelly; Davide Ascoli; Thomas Caignard; Francesco Chianucci; Elizabeth E. Crone; Emilie Fleurot; Jessie J. Foest; Georg Gratzer; Tomika Hagiwara; Qingmin Han; Valentin Journé; et al. (Trends in Ecology & Evolution, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Identification of ligands binding to MB327-PAM-1, a binding pocket relevant for resensitization of nAChRs - Jesko Kaiser; Christoph G.W. Gertzen; Tamara Bernauer; Valentin Nitsche; Georg Höfner; Karin V. Niessen; Thomas Seeger; Franz F. Paintner; Klaus T. Wanner; Dirk Steinritz; Franz Worek; Holger Gohlke (Toxicology Letters, 2024)

Synthesis and biological evaluation of novel MB327 analogs as resensitizers for desensitized nicotinic acetylcholine receptors after intoxication with nerve agents - Tamara Bernauer; Valentin Nitsche; Jesko Kaiser; Christoph G.W. Gertzen; Georg Höfner; Karin V. Niessen; Thomas Seeger; Dirk Steinritz; Franz Worek; Holger Gohlke; Klaus T. Wanner; Franz F. Paintner (Toxicology Letters, 2024)

Biogenic and lithogenic silicon along the GEOTRACES south West Indian Ocean section (SWINGS-GS02) and the islands mass effect on regional Si biogeochemical cycle - Valentin Deteix; Edwin Cotard; Sandrine Caquineau; William M. Landing; Frédéric Planchon; Thomas Ryan-Keogh; Damien Cardinal (Marine Chemistry, 2024)

Decomposing drivers in avian insectivory: Large‐scale effects of climate, habitat and bird diversity - Laura Schillé; Elena Valdés‐Correcher; Frédéric Archaux; Flavius Bălăcenoiu; Mona Chor Bjørn; Michal Bogdziewicz; Thomas Boivin; Manuela Branco; Thomas Damestoy; Maarten de Groot; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Journal of Biogeography, 2024)
Aim Climate is a major driver of large‐scale variability in biodiversity, as a likely result of more intense biotic interactions under warmer conditions. This idea fuelled decades of research on plant‐herbivore interactions, but much less is known about higher‐level trophic interactions. We addressed this research gap by characterizing both bird diversity and avian predation along a climatic gradient at the European scale. Location Europe. Taxon Insectivorous birds and pedunculate oaks. Methods We deployed plasticine caterpillars in 138 oak trees in 47 sites along a 19° latitudinal gradient in Europe to quantify bird insectivory through predation attempts. In addition, we used passive acoustic monitoring to (i) characterize the acoustic diversity of surrounding soundscapes; (ii) approximate bird abundance and activity through passive acoustic recordings; and (iii) infer both taxonomic and functional diversity of insectivorous birds from recordings. Results The functional diversity of insectivorous birds increased with warmer climates. Bird predation increased with forest cover and bird acoustic activity but decreased with mean annual temperature and functional richness of insectivorous birds. Contrary to our predictions, climatic clines in bird predation attempts were not directly mediated by changes in insectivorous bird diversity or acoustic activity, but climate and habitat still had independent effects on predation attempts. Main Conclusions Our study supports the hypothesis of an increase in the diversity of insectivorous birds towards warmer climates but refutes the idea that an increase in diversity would lead to more predation and advocates for better accounting for activity and abundance of insectivorous birds when studying the large‐scale variation in insect‐tree interactions.

Screening for new ligands of the MB327-PAM-1 binding site of the nicotinic acetylcholine receptor - Sonja Sichler; Georg Höfner; Valentin Nitsche; Karin V. Niessen; Thomas Seeger; Franz Worek; Franz F. Paintner; Klaus T. Wanner (Toxicology Letters, 2024)

Water resources availability in the Mefou basin, Cameroon: under current and future climate, and land use and land cover - Valentin Brice Ebodé; Jean Yannick Ngono Onana; Thomas Magloire Souga Boyomo (Sustainable Water Resources Management, 2024)

Interaction Between HCN and Slack Channels Regulates mPFC Pyramidal Cell Excitability in Working Memory Circuits - Jing Wu; Lynda El-Hassar; Dibyadeep Datta; Merrilee Thomas; Yalan Zhang; David P. Jenkins; Nicholas J. DeLuca; Manavi Chatterjee; Valentin K. Gribkoff; Amy F.T. Arnsten; Leonard K. Kaczmarek (Molecular Neurobiology, 2024)

LineaMapper: A deep learning-powered tool for mapping linear surface features on Europa - Caroline Haslebacher; Nicolas Thomas; Valentin T. Bickel (Icarus, 2024)

Availability of the current and future water resources in Equatorial Central Africa: case of the Nyong forest catchment in Cameroon - Valentin Brice Ebodé; Jean Yannick Ngono Onana; Jean Guy Dzana; Joseph Armathé Amougou; Romain Armand Soleil Batha; Thomas Magloire Souga Boyomo; Gaston Evarice Ndjela Mbeih (Environmental Monitoring and Assessment, 2024)

MS Binding Assays with UNC0642 as reporter ligand for the MB327 binding site of the nicotinic acetylcholine receptor - Valentin Nitsche; Georg Höfner; Jesko Kaiser; Christoph G.W. Gertzen; Thomas Seeger; Karin V. Niessen; Dirk Steinritz; Franz Worek; Holger Gohlke; Franz F. Paintner; Klaus T. Wanner (Toxicology Letters, 2024)

Spectroscopic investigation of diesel-piloted ammonia spray combustion - Valentin Scharl; Thomas Sattelmayer (Fuel, 2024)

Climate regulation processes are linked to the functional composition of plant communities in European forests, shrublands, and grasslands - Stephan Kambach; Fabio Attorre; Irena Axmanová; Ariel Bergamini; Idoia Biurrun; Gianmaria Bonari; Maria Laura Carranza; Alessandro Chiarucci; Milan Chytrý; Jürgen Dengler; Emmanuel Garbolino; Valentin Golub; et al. (Global Change Biology, 2024)
Terrestrial ecosystems affect climate by reflecting solar irradiation, evaporative cooling, and carbon sequestration. Yet very little is known about how plant traits affect climate regulation processes (CRPs) in different habitat types. Here, we used linear and random forest models to relate the community‐weighted mean and variance values of 19 plant traits (summarized into eight trait axes) to the climate‐adjusted proportion of reflected solar irradiation, evapotranspiration, and net primary productivity across 36,630 grid cells at the European extent, classified into 10 types of forest, shrubland, and grassland habitats. We found that these trait axes were more tightly linked to log evapotranspiration (with an average of 6.2% explained variation) and the proportion of reflected solar irradiation (6.1%) than to net primary productivity (4.9%). The highest variation in CRPs was explained in forest and temperate shrubland habitats. Yet, the strength and direction of these relationships were strongly habitat‐dependent. We conclude that any spatial upscaling of the effects of plant communities on CRPs must consider the relative contribution of different habitat types.

Development of a continuous silica treatment strategy for metal extraction processes in operating geothermal plants - Valentin Goldberg; Daniel Winter; Fabian Nitschke; Sebastian Held; Florian Groß; Daniel Pfeiffle; Jörg Uhde; Diego Morata; Joachim Koschikowski; Thomas Kohl (Desalination, 2023)

Single crystals of phenakite-like Be2(Si1−xGex)O4 solid solution: novel experimental data on hydrothermal crystal growth, X-ray diffraction and Raman spectroscopy study - Valentin Kovalev; Victor Thomas; Tatiana Setkova; Natalia Zubkova; Anna Spivak; Dmitry Fursenko; Vasiliy Yapaskurt; Alexander Antipin; Elena Borovikova (Physics and Chemistry of Minerals, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Change detection and monitoring of active Martian surface phenomena with the Colour and Stereo Surface Imaging System (CaSSIS) onboard the ExoMars Trace Gas Orbiter (TGO) - Vidhya Ganesh Rangarajan; Livio L. Tornabene; Gordon R. Osinski; Susan J. Conway; Frank P. Seelos; Simone Silvestro; Francesco Salese; Maurizio Pajola; Alice Lucchetti; Giovanni Munaretto; Valentin T. Bickel; Nicolas Thomas; et al. (Icarus, 2023)

A multiscale ocean modelling system for the central Arabian/Persian Gulf: From regional to structure scale circulation patterns - Emmanuel Hanert; Aboobacker Valliyil Mohammed; Subramanian Veerasingam; Thomas Dobbelaere; Valentin Vallaeys; Ponnumony Vethamony (Estuarine, Coastal and Shelf Science, 2023)

Phasing with near rectilinear Halo orbits: Design and comparison - Giordana Bucchioni; Stephanie Lizy-Destrez; Thomas Vaujour; Valentin Thoraval; Léa Rouverand; Catarina Silva (Advances in Space Research, 2023)

Characterization of ammonia spray combustion and mixture formation under high-pressure, direct injection conditions - Valentin Scharl; Tomislav Lackovic; Thomas Sattelmayer (Fuel, 2023)

Porosity, strength, and alteration – Towards a new volcano stability assessment tool using VNIR-SWIR reflectance spectroscopy - Gabor Kereszturi; Michael Heap; Lauren N. Schaefer; Herlan Darmawan; Frances M. Deegan; Ben Kennedy; Jean-Christophe Komorowski; Stuart Mead; Marina Rosas-Carbajal; Amy Ryan; Valentin R. Troll; Marlène Villeneuve; et al. (Earth and Planetary Science Letters, 2023)

Combination of close-range and aerial photogrammetry with terrestrial laser scanning to answer microbiological and climatological questions in connection with lava caves - Michael Kögel; Andreas Pflitsch; Diana E. Northup; Dirk Carstensen; Joseph J. Medley; Teresa Mansheim; Thomas Killing; Michael Buschbacher; Helena Angerer; Julian Falkner; Achilleas Kynatidis; Valentin Ott; et al. (Applied Geomatics, 2022)
Combining photogrammetric reconstruction (close-range photogrammetry, CRP) and airborne photogrammetry through the structure from motion method (SFM) with terrestrial three-dimensional (3D) laser scanning (TLS), Maelstrom Cave on Big Island, Hawaii (USA), was mapped in three dimensions. The complementary properties of the two methods generated an overall model that depicted significant features of the cave both spatially and visually. Through various processes, the complex geometric quantities were derived from the model that can be used to answer microbiological and climatological questions. In this report, the procedure for the three-dimensional acquisition of the terrain surface above Maelstrom Cave as well as the interior of the cave with TLS and SFM is described. It is shown how the different data sets were combined and contrasted, including a comparison of geometries from the different survey operations. Finally, the editing processes used to quantify and simplify the cave geometry are presented, as well as the analysis of the ellipses generated accordingly to determine the geometric quantities. Through the analysis of the cave geometry, important geometric properties of the Maelstrom Cave could be quantified and categorized. In this way, an effective tool was developed to directly correlate the structure of the cave system with climatological and microbiological parameters in order to answer the corresponding questions.

Drivers of soil respiration across a management intensity gradient in temperate grasslands under drought - Antonios Apostolakis; Ingo Schöning; Beate Michalzik; Valentin H. Klaus; Runa S. Boeddinghaus; Ellen Kandeler; Sven Marhan; Ralph Bolliger; Markus Fischer; Daniel Prati; Falk Hänsel; Thomas Nauss; et al. (Nutrient Cycling in Agroecosystems, 2022)
Soil respiration is an important pathway of soil organic carbon losses in temperate grasslands; however, it is rarely studied across broad management intensity gradients in a landscape. Using the soda-lime method, we measured in-situ soil CO 2 efflux with single measurements of long exposure time (i.e. 3 day long) in 150 grasslands in three German regions in early summer 2018 and 2019. The grasslands ranged from unfertilized and grazed grasslands to intensively fertilized and frequently harvested ones. To assess effects of grazing and fertilization intensities and plant diversity on soil CO 2 efflux, we used Structural Equation Modeling to account for direct effects and indirect effects through soil and plant organic matter quantity and quality. Soil CO 2 efflux was suppressed by limited water availability caused by naturally occurring droughts in both study years. Under the prevailing environmental conditions, grazing intensity, plant biomass and plant C:N ratio were not related to soil CO 2 efflux. In contrast, fertilization intensity was positively associated with soil CO 2 efflux (standardized coefficient of net effect: + 0.04 in 2018 and + 0.03 in 2019). This was because fertilization led to lower plant species richness and, thus, to lower C:N ratios in soils, which were associated with higher soil CO 2 efflux (plant species richness net effect: −0.09 in 2018 and −0.18 in 2019; soil C:N ratio direct effect: −0.23 in 2018 and −0.33 in 2019). Intensively managed grasslands have higher soil respiration than extensively managed, plant species-rich grasslands even under the extreme conditions of natural droughts.

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Binding Stability of Antibody—α-Synuclein Complexes Predicts the Protective Efficacy of Anti-α-synuclein Antibodies - Matthias Höllerhage; Andreas Wolff; Tasnim Chakroun; Valentin Evsyukov; Linghan Duan; Oscar Wing-Ho Chua; Qilin Tang; Thomas Koeglsperger; Günter U. Höglinger (Molecular Neurobiology, 2022)
Spreading of alpha-synuclein (αSyn) may play an important role in Parkinson’s disease and related synucleinopathies. Passive immunization with anti-αSyn antibodies is a promising method to slow down the spreading process and thereby the progression of synucleinopathies. Currently, it remains elusive which specific characteristics are essential to render therapeutic antibodies efficacious. Here, we established a neuronal co-culture model, in which αSyn species are being released from αSyn-overexpressing cells and induce toxicity in a priori healthy GFP-expressing cells. In this model, we investigated the protective efficacy of three anti-αSyn antibodies. Only two of these antibodies, one C-terminal and one N-terminal, protected from αSyn-induced toxicity by inhibiting the uptake of spreading-competent αSyn from the cell culture medium. Neither the binding epitope nor the affinity of the antibodies towards recombinant αSyn could explain differences in biological efficacy. However, both protective antibodies formed more stable antibody-αSyn complexes than the non-protective antibody. These findings indicate that the stability of antibody-αSyn complexes may be more important to confer protection than the binding epitope or affinity to recombinant αSyn.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Leaf phenology correlates with fruit production in European beech (Fagus sylvatica) and in temperate oaks (Quercus robur and Quercus petraea) - Valentin Journé; Thomas Caignard; Andrew Hacket-Pain; Michał Bogdziewicz (European Journal of Forest Research, 2021)

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe - Elena Valdés‐Correcher; Xoaquín Moreira; Laurent Augusto; Luc Barbaro; Christophe Bouget; Olivier Bouriaud; Manuela Branco; Giada Centenaro; György Csóka; Thomas Damestoy; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Global Ecology and Biogeography, 2021)
Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur . Methods We simultaneously tested for latitudinal variation in plant–herbivore–natural enemy interactions. We further investigated the underlying climatic factors associated with variation in herbivory, leaf chemistry and attack rates in Quercus robur across its complete latitudinal range in Europe. We quantified insect leaf damage and the incidence of specialist herbivores as well as leaf chemistry and bird attack rates on dummy caterpillars on 261 oak trees. Results Climatic factors rather than latitude per se were the best predictors of the large‐scale (geographical) variation in the incidence of gall‐inducers and leaf‐miners as well as in leaf nutritional content. However, leaf damage, plant chemical defences (leaf phenolics) and bird attack rates were not influenced by climatic factors or latitude. The incidence of leaf‐miners increased with increasing concentrations of hydrolysable tannins, whereas the incidence of gall‐inducers increased with increasing leaf soluble sugar concentration and decreased with increasing leaf C : N ratios and lignins. However, leaf traits and bird attack rates did not vary with leaf damage. Main conclusions These findings help to refine our understanding of the bottom‐up and top‐down mechanisms driving geographical variation in plant–herbivore interactions, and indicate the need for further examination of the drivers of herbivory on trees.

Adaptive divergence across Southern Ocean gradients in the pelagic diatom Fragilariopsis kerguelensis - Ute Postel; Barbara Glemser; Katherine Salazar Alekseyeva; Sarah Lena Eggers; Marco Groth; Gernot Glöckner; Uwe John; Thomas Mock; Kerstin Klemm; Klaus Valentin; Bánk Beszteri (Molecular Ecology, 2020)
The Southern Ocean is characterized by longitudinal water circulations crossed by strong latitudinal gradients. How this oceanographic background shapes planktonic populations is largely unknown, despite the significance of this region for global biogeochemical cycles. Here, we show, based on genomic, morphometric, ecophysiological and mating compatibility data, an example of ecotypic differentiation and speciation within an endemic pelagic inhabitant, the diatom Fragilariopsis kerguelensis . We discovered three genotypic variants, one present throughout the latitudinal transect sampled, the others restricted to the north and south, respectively. The latter two showed reciprocal monophyly across all three genomes and significant ecophysiological differences consistent with local adaptation, but produced viable offspring in laboratory crosses. The third group was also reproductively isolated from the latter two. We hypothesize that this pattern originated by an adaptive expansion accompanied by ecotypic divergence, followed by sympatric speciation.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

Homogeneity assessment of phenological records from the Swiss Phenology Network - Yuri Brugnara; Renate Auchmann; This Rutishauser; Regula Gehrig; Barbara Pietragalla; Michael Begert; Christian Sigg; Valentin Knechtl; Thomas Konzelmann; Bertrand Calpini; Stefan Brönnimann (International Journal of Biometeorology, 2020)

Management of Grassland-like Wildflower Strips Sown on Nutrient-rich Arable Soils: The Role of Grass Density and Mowing Regime - Julien Piqueray; Valentin Gilliaux; Virginie Decruyenaere; Jean-Thomas Cornelis; Roel Uyttenbroeck; Grégory Mahy (Environmental Management, 2019)

Heterocycles 44. Synthesis, characterization and anticancer activity of new thiazole ortho-hydroxychalcones - Fana-Maria Coman; Armelle T. Mbaveng; Denisa Leonte; László Csaba Bencze; Laurian Vlase; Silvia Imre; Victor Kuete; Thomas Efferth; Valentin Zaharia (Medicinal Chemistry Research, 2018)

A robust and accurate surrogate method for monitoring the frequency and duration of combined sewer overflows - Thomas Hofer; Albert Montserrat; Guenter Gruber; Valentin Gamerith; Lluis Corominas; Dirk Muschalla (Environmental Monitoring and Assessment, 2018)

Converging Climate Sensitivities of European Forests Between Observed Radial Tree Growth and Vegetation Models - Zhen Zhang; Flurin Babst; Valentin Bellassen; David Frank; Thomas Launois; Kun Tan; Philippe Ciais; Benjamin Poulter (Ecosystems, 2018)

Spatial and temporal dynamics in the Phialocephala fortinii s.l. – Acephala applanata species complex (PAC) - Sophie Stroheker; Valentin Queloz; Thomas N. Sieber (Plant and Soil, 2016)

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

Improving resistance to the European corn borer: a comprehensive study in elite maize using QTL mapping and genome-wide prediction - Flavio Foiada; Peter Westermeier; Bettina Kessel; Milena Ouzunova; Valentin Wimmer; Wolfgang Mayerhofer; Thomas Presterl; Michael Dilger; Ralph Kreps; Joachim Eder; Chris-Carolin Schön (Theoretical and Applied Genetics, 2015)

Pathogenesis of adult-onset Still’s disease: new insights from the juvenile counterpart - Yvan Jamilloux; Mathieu Gerfaud-Valentin; Fabio Martinon; Alexandre Belot; Thomas Henry; Pascal Sève (Immunologic Research, 2015)

Olfactory bulb volume in smokers - Valentin A. Schriever; Nicole Reither; Johannes Gerber; Emilia Iannilli; Thomas Hummel (Experimental Brain Research, 2013)

No biogeographical pattern for a root‐associated fungal species complex - Valentin Queloz; Thomas N. Sieber; Ottmar Holdenrieder; Bruce A. McDonald; Christoph R. Grünig (Global Ecology and Biogeography, 2011)
Aim The biogeography of microbes is poorly understood and there is an open debate regarding if and how microbial biodiversity is structured. At the beginning of the 20th century, Baas Becking laid the foundations for the biogeography of microbes by stating that ‘Everything is everywhere, but the environment selects’ (the EisE hypothesis). This hypothesis remained dogma for almost a century. However, the recognition that microbial ‘species’ are often assemblages of reproductively isolated lineages challenged the EisE hypothesis, leading to the now common assumption that microbial communities possess cryptic biogeographic structures. We tested the presence of a cryptic biogeographical structure for a well‐characterized fungal species complex (the Phialocephala fortinii s.l.– Acephala applanata species complex, PAC) using precise molecular species resolution. In addition, we analysed factors that could govern PAC community assembling. Locations Forty‐four study sites in temperate and boreal forests across the Northern Hemisphere were included. Methods (1) The distance–decay relationship among PAC communities was calculated and a resampling procedure was applied to analyse the effect of sampling intensity and geographic distances among PAC communities. (2) Factors shaping PAC communities (e.g. climatic factors and tree species composition) were studied. (3) We tested PAC communities for random composition. Results We found that the similarity of species assemblages did not decrease with increasing geographical distance. Moreover, species diversity did not increase by expanding the area sampled. Instead, species diversity increased by increasing the sampling effort. Community composition correlated neither with tree species composition nor climate, and no association among species was observed. Main conclusions We could not discover any cryptic biogeographic structure even after applying refined species assignment but we demonstrate the importance of sampling effort for understanding the biogeography of microorganisms. Moreover, we show that primarily stochastic effects are responsible for the species composition of PAC communities.

Gaudeamus lavocati sp. nov. (Rodentia, Hystricognathi) from the early Oligocene of Zallah, Libya: first African caviomorph? - Pauline Coster; Mouloud Benammi; Vincent Lazzari; Guillaume Billet; Thomas Martin; Mustafa Salem; Awad Abolhassan Bilal; Yaowalak Chaimanee; Mathieu Schuster; Xavier Valentin; Michel Brunet; Jean-Jacques Jaeger (The Science of Nature, 2010)

Antifreeze proteins in polar sea ice diatoms: diversity and gene expression in the genus Fragilariopsis - Maddalena Bayer‐Giraldi; Christiane Uhlig; Uwe John; Thomas Mock; Klaus Valentin (Environmental Microbiology, 2010)
Summary Fragilariopsis is a dominating psychrophilic diatom genus in polar sea ice. The two species Fragilariopsis cylindrus and Fragilariopsis curta are able to grow and divide below freezing temperature of sea water and above average sea water salinity. Here we show that antifreeze proteins (AFPs), involved in cold adaptation in several psychrophilic organisms, are widespread in the two polar species. The presence of AFP genes ( afp s) as a multigene family indicated the importance of this group of genes for the genus Fragilariopsis , possibly contributing to its success in sea ice. Protein phylogeny showed the potential mobility of afp s, which appear to have crossed kingdom and domain borders, occurring in Bacteria , diatoms, crustaceans and fungi. Our results revealed a broad distribution of AFPs not only in polar organisms but also in taxa apparently not related to cold environments, suggesting that these proteins may be multifunctional. The relevance of AFPs to Fragilariopsis was also shown by gene expression analysis. Under stress conditions typical for sea ice, with subzero temperatures and high salinities, F. cylindrus and F. curta strongly expressed selected afp s. An E/G point mutation in the Fragilariopsis AFPs may play a role in gene expression activity and protein function.

Report and Recommendations of the Workshop of the European Centre for the Validation of Alternative Methods for Drug-Induced Cardiotoxicity - Tina C. Stummann; Mario Beilmann; Göran Duker; Berengere Dumotier; J. Magnus Fredriksson; Robin L. Jones; Marina Hasiwa; Y. James Kang; Carl-Fredrik Mandenius; Thomas Meyer; Giorgio Minotti; Y. Jean-Pierre Valentin; et al. (Cardiovascular Toxicology, 2009)

Large-scale failures on domes and stratocones situated on caldera ring faults: sand-box modeling of natural examples from Kamchatka, Russia - Alexander Belousov; Thomas R. Walter; Valentin R. Troll (Bulletin of Volcanology, 2005)

Formation of caldera periphery faults: an experimental study - Thomas R. Walter; Valentin R. Troll (Bulletin of Volcanology, 2001)

Role of acylCoA binding protein in acylCoA transport, metabolism and cell signaling - Jens Knudsen; Mette Valentin Jensen; Nils J. F\sgmaelig; rgeman; Thomas B.F. Neergaard; Barbara Gaigg (Molecular and Cellular Biochemistry, 1999)